Effect of intraperitoneally administered hydrolyzed whey protein on blood pressure and renal sodium handling in awake spontaneously hypertensive rats - Costa,E.L. (2005)
The present study evaluated the acute effect of the intraperitoneal (ip) administration of a whey protein hydrolysate (WPH) on systolic arterial blood pressure (SBP) and renal sodium handling by conscious spontaneously hypertensive rats (SHR). The ip administration of WPH in a volume of 1 ml dose-dependently lowered the SBP in SHR 2 h after administration at doses of 0.5 g/kg (0.15 M NaCl: 188.5 ± 9.3 mmHg vs WPH: 176.6 ± 4.9 mmHg, N = 8, P = 0.001) and 1.0 g/kg (0.15 M NaCl: 188.5 ± 9.3 mmHg vs WPH: 163.8 ± 5.9 mmHg, N = 8, P = 0.0018). Creatinine clearance decreased significantly (P = 0.0084) in the WPH-treated group (326 ± 67 µL min-1 100 g body weight-1) compared to 0.15 M NaCl-treated (890 ± 26 µL min-1 100 g body weight-1) and captopril-treated (903 ± 72 µL min-1 100 g body weight-1) rats. The ip administration of 1.0 g WPH/kg also decreased fractional sodium excretion to 0.021 ± 0.019% compared to 0.126 ± 0.041 and 0.66 ± 0.015% in 0.15 M NaCl and captopril-treated rats, respectively (P = 0.033). Similarly, the fractional potassium excretion in WPH-treated rats (0.25 ± 0.05%) was significantly lower (P = 0.0063) than in control (0.91 ± 0.15%) and captopril-treated rats (1.24 ± 0.30%), respectively. The present study shows a decreased SBP in SHR after the administration of WPH associated with a rise in tubule sodium reabsorption despite an angiotensin I-converting enzyme (ACE)-inhibiting in vitro activity (IC50 = 0.68 mg/mL). The present findings suggest a pathway involving ACE inhibition but measurements of plasma ACE activity and angiotensin II levels are needed to support this suggestion.